2013
DOI: 10.1016/j.nicl.2013.03.016
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructural abnormalities in bipolar disorder: A whole brain diffusion tensor imaging study

Abstract: BackgroundBipolar disorder (BD) is a chronic mental illness characterized by severe disruptions in mood and cognition. Diffusion tensor imaging (DTI) studies suggest that white matter (WM) tract abnormalities may contribute to the clinical hallmarks of the disorder. Using DTI and whole brain voxel-based analysis, we mapped the profile of WM anomalies in BD. All patients in our sample were euthymic and lithium free when scanned.MethodsDiffusion-weighted and T1-weighted structural brain images were acquired from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
63
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 98 publications
9
63
0
2
Order By: Relevance
“…In addition, these images align with Barysheva et al [4] and Thomason and Thompson [5] who also reported atrophy in callosum and cortical association fibers in euthymic patients with bipolar disorder. Specifically, the lack of connectivity in the genu and splenium corpus callosi and in the frontal areas shown in this case series mirror the available data [3][4][5] and suggest that DTI may help to neurologically characterize bipolar illness.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, these images align with Barysheva et al [4] and Thomason and Thompson [5] who also reported atrophy in callosum and cortical association fibers in euthymic patients with bipolar disorder. Specifically, the lack of connectivity in the genu and splenium corpus callosi and in the frontal areas shown in this case series mirror the available data [3][4][5] and suggest that DTI may help to neurologically characterize bipolar illness.…”
Section: Discussionsupporting
confidence: 84%
“…The lifetime rate of substance abuse in those with bipolar disorder is about 60% with half of this subset addicted to cocaine [2]. In the past decade, diffusion tensor imaging (DTI) techniques have provided mounting evidence showing that atrophied white matter tracks primarily in the corpus callosi and frontocortical areas are common in bipolar disorder without cocaine abuse [3][4][5]. Others find corpus callous and orbitofrontal areas with white matter atrophy in those with cocaine abuse without bipolar illness [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although findings are heterogeneous, the most consistent findings have been of decreased FA and/or increased mean diffusivity (MD) in limbic-striatal, callosal and prefrontal regions in adults (Barysheva et al, 2013). FA represents the fraction of the tensor that can be assigned to anisotropic diffusion, and is sensitive to structural differences in myelination, axonal density, axonal caliber and fiber coherence (Cheng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…DTI produces FA as a measure of the orientational coherence of water diffusion. Low FA values may suggest loss of white matter integrity, decrease in axonal density, or disorganization of axonal structure (18)(19).…”
Section: Discussionmentioning
confidence: 99%